1992
DOI: 10.1007/bf03217233
|View full text |Cite
|
Sign up to set email alerts
|

Some cognitive factors relevant to mathematics instruction

Abstract: Our understanding of cognitive processes has progressed sufficiently in the last few years to enable us to generate novel instructional techniques that can enhance substantially learning of subjects such as mathematics. This paper will review briefly some research intended to contribute to this process. There are two relevant aspects. Firstly, recent work has thrown light on schema acquisition while learning mathematics, and on techniques for detecting schemas in mathematics learners. Secondly, other research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Their line of research has shown that explicit instruction in problem-solution and schema-broadening instruction as well as self-regulated learning strategies is necessary to enhance mathematical problem-solving performance. However, none of these studies examined the long-term effects of schema-mediated instruction or the benefits of visual representation techniques, such as those involving diagrams, that are helpful scaffolds in organizing information in the problem, thereby reducing the level of cognitive load associated with the problem-solving task (Pawley, Ayres, Cooper, & Sweller, 2005;Sweller & Low, 1992;Sweller, Van Merrienboer, & Paas, 1998).…”
Section: Relevant Researchmentioning
confidence: 99%
“…Their line of research has shown that explicit instruction in problem-solution and schema-broadening instruction as well as self-regulated learning strategies is necessary to enhance mathematical problem-solving performance. However, none of these studies examined the long-term effects of schema-mediated instruction or the benefits of visual representation techniques, such as those involving diagrams, that are helpful scaffolds in organizing information in the problem, thereby reducing the level of cognitive load associated with the problem-solving task (Pawley, Ayres, Cooper, & Sweller, 2005;Sweller & Low, 1992;Sweller, Van Merrienboer, & Paas, 1998).…”
Section: Relevant Researchmentioning
confidence: 99%
“…This research has been generated by the following assumptions concerning our basic cognitive architecture: (a) People have a very limited working memory that is able to hold and process only a few items of information at a time; (b) People have a huge long-term memory that is effectively unlimited in size; (c) Schema acquisition is a primary learning mechanism. Schemata are defined as cognitive constructs that permit people to categorize information in the manner in which it will be used (see Low & Over, 1990, 1992; Low, Over, Doolan, & Michell, 1994; Sweller & Low, 1992). Schemata have the functions of storing information in long-term memory and of reducing working memory load by permitting people to treat multiple elements of information as a single element; (d) Automation of cognitive processes, including automatic use of schemata, is a learning mechanism that also reduces working memory load by effectively bypassing working memory.…”
mentioning
confidence: 99%